Peran Kantor Jasa Akuntan Dalam Peningkatan Kualitas Informasi Blud Puskesmas - Kamila Kamila; Lia Eriska Br Sitepu; Annisa Putri Ramadani; Muhammad Angga Reksa; Putri Faradilla (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Health development is aimed at increasing the highest degree of public health. District Health Centeris a spearhead health service facility. The implementation of health services requires the management of integrated, sustainable health centers to produce effective and efficient health center performance in the form of human resources, infrastructure and budgets with the Implementation of Financial Management of Regional Public Service Agencies (BLUD). The problem in this research is the lack of effective application of financial management of the Regional Public Service Agency (BLUD) District Health Center, Bandung in improving service performance, Health Service variables in Performance Assessment are still in sufficient category. The implementation of the BLUD Financial Management Pattern can be said to be effective if it has fulfilled eight criteria in measuring the effectiveness of a program in accordance with Siagian's theory, namely: clarity of purpose, clarity of strategy to achieve goals, steady analysis and policy formulation, careful planning, proper programming, availability facilities and infrastructure activities, effective and efficient implementation, supervision and control. Keywords: Health Services, BLUD Financial Management